Assessment of the Implementation of Respectful Maternity Care Charter in North Central Nigeria (Federal Capital Territory and Kwara State): Study Protocol - Tanimola Akande,; Abiodun Adeniran,; Omotayo Adesiyun,; Mojirola Fasiku,; Maryam Jimoh,; Ugo Okoli,; Elizabeth Chukwu,; Hannah Tappis,; Kathleen Hills,; Anthony Adoghe,; Ayoola Olushola,; Oluwadamilola Olaogun,; et al. (AlQalam Journal of Medical and Applied Sciences, 2024)
Respectful Maternity Care (RMC) charter is one of the tools for ensuring quality of care in maternity services. Nigeria is a signatory to RMC charter; therefore, the charter is expected to be the standard of care. However, in Nigeria and other countries, reports of disrespectful maternity care abound; this discourages women from accessing facility-birth. Therefore, to improve the quality of care towards increase in uptake, it is expedient to assess the level of implementation of the RMC charter by key stakeholders for sustainability, impact and scale-up of charter-compliant maternity care in Nigeria. The study aims to assess the implementation of RMC charter in North-central Nigeria. The study is a mixed-method, cross-sectional study; the expected participants are key stakeholders in healthcare (Healthcare workers, Healthcare Administrators, Project Managers, Policy makers) in North-Central Nigeria (Federal Capital Territory and Kwara state). A multistage sampling technique would be used to enroll participants from 18 healthcare facilities (Primary, Private, Secondary and Tertiary) in rural and urban areas and Ministries of Health officials at local and state government levels. Expected outcomes: The study is expected to provide information on the current status of knowledge and implementation of the RMC charter in Nigeria. It would also identify the enablers and barriers to the implementation process and provide evidence for effective scale-up of the process in Nigeria. The outcomes will be widely disseminated to healthcare workers, health administrators and decision-makers in healthcare services through post-study meetings, conference presentations, journal publications and policy briefs for effective RMC charter implementation in Nigeria. يعد ميثاق رعاية الأمومة المحترمة إحدى الأدوات لضمان جودة الرعاية في خدمات الأمومة. نيجيريا هي إحدى الدول الموقعة على ميثاق رعاية الأمومة المحترمة. لذلك من المتوقع أن يكون الميثاق هو معيار الرعاية. ومع ذلك، في نيجيريا وبلدان أخرى، تكثر التقارير عن رعاية الأمومة غير المحترمة؛ وهذا لا يشجع النساء على الوصول إلى مرافق الولادة. لذلك، لتحسين جودة الرعاية من أجل زيادة استيعابها، من المناسب تقييم مستوى تنفيذ ميثاق رعاية الأمومة المحترمة من قبل أصحاب المصلحة الرئيسيين من أجل الاستدامة والتأثير وتوسيع نطاق رعاية الأمومة المتوافقة مع الميثاق في نيجيريا. تهدف الدراسة إلى تقييم تنفيذ ميثاق رعاية الأمومة المحترمة في شمال وسط نيجيريا. الدراسة عبارة عن دراسة مقطعية مختلطة المنهج؛ المشاركون المتوقعون هم أصحاب المصلحة الرئيسيون في مجال الرعاية الصحية (العاملون في مجال الرعاية الصحية، ومديرو الرعاية الصحية، ومديرو المشاريع، وواضعو السياسات) في شمال وسط نيجيريا (إقليم العاصمة الفيدرالية وولاية كوارا). سيتم استخدام تقنية أخذ العينات متعددة المراحل لتسجيل المشاركين من 18 منشأة للرعاية الصحية (الابتدائية والخاصة والثانوية والثالثية) في المناطق الريفية والحضرية ومسؤولي وزارات الصحة على المستوى المحلي ومستوى حكومات الولايات. النتائج المتوقعة: من المتوقع أن تقدم الدراسة معلومات عن الوضع الحالي للمعرفة وتنفيذ ميثاق رعاية الأمومة المحترمة في نيجيريا. كما أنه سيحدد عوامل التمكين والحواجز التي تعترض عملية التنفيذ ويقدم الأدلة لتوسيع نطاق العملية بشكل فعال في نيجيريا. سيتم نشر النتائج على نطاق واسع للعاملين في مجال الرعاية الصحية ومديري الصحة وصناع القرار في خدمات الرعاية الصحية من خلال اجتماعات ما بعد الدراسة وعروض المؤتمرات ومنشورات المجلات وموجزات السياسات من أجل التنفيذ الفعال لميثاق رعاية الأمومة المحترمة في نيجيريا.